Lite-CA based key pre-distribution scheme in wireless sensor network - PAN Yun1; WANG Li-cheng2; CAO Zhen-fu3; LI Jian2 (Tongxin xuebao)
Large-scale sensor nodes were usually deployed in potentially adverse or even hostile environment, so the security in these networks was very important.Due to its constraints on node cost, size and power dissipation, sensor’s energy and capabilities on computation, storage and communication were considerably weak compared with general computers.It leaded to many new challenges for designing of key management protocols in WSN.Therefore, a lite-CA based key pre-distribution scheme was suggested.The traits of CA-based authentication framework and identity-based authentication framework were combined by this scheme.Further, the scheme was efficiently implemented based on quadratic residue theory.